Donor nerve graft assessment for covering thumb nerve defects: a cadaveric study - Hamid Namazi; Ahmad Sobhani; Saeed Gholamzadeh; Amirreza Dehghanian; Fatemeh Dehghani Nazhvani (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Background Even though several studies reported donor autologous nerve grafts for digital nerve defects, there is no report in the literature regarding acceptable graft for thumb nerves. The purpose of this study is to provide guidelines for autologous nerve graft selection by detecting similarities between thumb nerve zones and donor nerve with regard to the number of fascicles and cross-sectional area. Materials and methods Five cadavers were used in this study. An anatomical zoning system was defined for thumb nerves (zones 1, 2, 3). Sural nerve (SN), medial antebrachial cutaneous nerve (MABCN), lateral antebrachial cutaneous nerve (LABCN), posterior interosseous nerve (PIN), and anterior interosseous nerve (AIN) were selected as donor nerve grafts. The number of fascicles and surface area (mm2) was defined. Results The mean of the fascicle number in zone 1, zone 2, zone 3, AIN, PIN, LABCN, MABCN, and SN were 3.8, 4.7, 6.1, 2.2, 1.8, 4.5, 3.1, and 6.4, respectively. The mean of the surface area in zone 1, zone 2, zone 3, AIN, PIN, LABCN, MABCN, and SN were 2.19, 6.26, 4.04, 1.58, 0.71, 5.00, 3.01, and 8.06, respectively. Conclusions LABCN is the best choice for all zones that has fascicular matching with all three zones of thumb nerves and caliber matching with zones 2 and 3. In zone 1, the best nerve graft is MABCN which has both suitable caliber and fascicle count.